Design and Experimental Evaluation of a Low-Cost Rogue Access Point Based on SOHO Hardware - Piotr Augustyniak; Mateusz Boch; Piotr Zwierzykowski (Communications of International Proceedings, 2025)
This paper presents the hardware and software possibilities of constructing a Rogue Access Point (RAP) using commonly available SOHO-class devices. The work has an analytical and experimental character and focuses on assessing the practicality of low-cost solutions, selection criteria, and limitations resulting from the use of open-source firmware. The research replicates audit functionalities inspired by the Wi-Fi Pineapple platform using a TP-Link Archer C7 v2 router with OpenWrt. The results demonstrate both the feasibility and limitations of such an approach, highlighting stability, compatibility, and operational issues. The paper also discusses the implications of RAP attacks and provides recommendations for further security-oriented research.
Keywords: Rogue Access Point; SOHO router; OpenWrt; Wi-Fi Pineapple; network security; captive portal; deauthentication.